Integrating diversity into the medical curriculum - Shrivastava, Saurabh R; Shrivastava, Prateek S; Joshi, Ahishek (Indian Journal of Community Health, 2023)
In the field of medical education, diversity refers to the presence and representation of persons from a diversified range of personal backgrounds, experiences, and characteristics across the student community, faculty members, and employees in the institution. The scope of diversity in medical education is immense and it plays a vital role in creating an effective learning environment. Once students are exposed to a group of diverse students and patients during their undergraduate training, there is a significant improvement in cultural competence, which becomes crucial in our mission to deliver patient-centered care. Considering the merits of diversity in the medical curriculum for medical students, there is an indispensable need to take specific measures to ensure that diversity is integrated in the curriculum, as it will also ensure the delivery of equitable and culturally competent medical care. As important is to ensure the integration of diversity into medical curriculum, equal importance has to be given to the measurement of various initiatives that have been taken to promote diversity in medical education. In conclusion, diversity in medical education is the need of the hour to create a fruitful learning environment for medical students. This calls for the need to take measures for the integration of diversity into the medical curriculum and subsequently identify strategies and indicators to measure and monitor the progress of diversity initiatives in medical institutions.